Urine output as one of the most important features in differentiating in-hospital death among patients receiving extracorporeal membrane oxygenation: a random forest approach - Chang, Sheng-Nan; Hu, Nian-Ze; Wu, Jo-Hsuan; Cheng, Hsun-Mao; Caffrey, James L.; Yu, Hsi-Yu; Chen, Yih-Sharng; Hsu, Jiun; Lin, Jou-Wei (European journal of medical research, 2023)
Background It is common to support cardiovascular function in critically ill patients with extracorporeal membrane oxygenation (ECMO). The purpose of this study was to identify patients receiving ECMO with a considerable risk of dying in hospital using machine learning algorithms. Methods A total of 1342 adult patients on ECMO support were randomly assigned to the training and test groups. The discriminatory power (DP) for predicting in-hospital mortality was tested using both random forest (RF) and logistic regression (LR) algorithms. Results Urine output on the first day of ECMO implantation was found to be one of the most predictive features that were related to in-hospital death in both RF and LR models. For those with oliguria, the hazard ratio for 1 year mortality was 1.445 ( p < 0.001, 95% CI 1.265–1.650). Conclusions Oliguria within the first 24 h was deemed especially significant in differentiating in-hospital death and 1 year mortality.